Examining citizenship participation in young Australian adults: a structural equation analysis - Yeung, Polly; Passmore, Anne; Packer, Tanya (Routledge, 2012)
As citizens, young adults should be supported and encouraged to enact their basic rights and responsibilities to partake in decision-making that affects their lives and development. Recent studies in several Western countries, including Australia, have suggested that levels of political and community activities among young adults have significantly decreased. This study tested a theoretically and empirically based explanatory model of citizenship participation on 434 young Australian adults to examine how the variables of social milieu, citizen communication networks, self-efficacy and life satisfaction contributed to citizenship participation (social and civic activities). Structural equation modelling corroborated a meditational model in which citizen communication networks and social milieu accounted for significant variance in self-efficacy and life satisfaction which in turn accounted for social and civic participation. Results demonstrated that citizenship participation is influenced by the social environment, which is multidimensional and the person–environment interaction is subject to ongoing changes. Young adults' social contexts are important socialising agents that promote citizenship participation.